A brief review on utilizing natural adsorbents for microplastic removal from wastewater: A sustainable approach to environmental protection - Esmaeil Allahkarami; Ebrahim Allahkarami; Bahram Rezai (Results in Engineering)
Microplastics—plastic particles no larger than 5 mm—have become widespread in aquatic environments due to extensive pollution from this material. Microplastics have emerged as a global environmental concern due to their persistence, bioaccumulation potential, and ecological toxicity. This review systematically explores the potential of natural adsorbents—including biochar, clay minerals, natural fibers, algae, and agricultural waste—for the removal of microplastics from aquatic environments. The adsorption mechanisms involved (e.g., electrostatic interactions, hydrophobic binding, and pore entrapment) are critically examined. Reported removal efficiencies vary widely, with some biochar and clay-based materials achieving over 80 % microplastic removal under laboratory conditions. Key advantages such as cost-effectiveness, availability, and eco-compatibility are discussed alongside limitations like adsorbent regeneration and performance variability. Finally, the review highlights future research directions focusing on enhancing adsorption efficiency, scaling up treatment processes, and ensuring environmental safety. The findings support the integration of natural adsorbents into sustainable wastewater treatment solutions for microplastic mitigation.